The Effect of Kendo’s Chudan-no-kamae and Three Striking Movements on Changes in Brainwaves Related to Concentration Index - Shin, Yun-A; Hong, Sang-Min; Kim, Seung-Ho; Lee, Byung-Kun (The Asian journal of kinesiology, 2021)
OBJECTIVES This study was conducted to figure out the effects of kendo training on the activity of brainwaves by analyzing changes in brainwaves during chudan-no-kamae and three-movement-striking, which are basic movements of kendo, in elementary school students who undergo kendo training and comparing left and right side brainwave activities to find out differences.METHODS This study was conducted with 29 male elementary school students living in K City who were experts in kendo with a career as an athlete or a kendo training period not shorter than six months. The brainwave activity was measured by measuring and analyzing brainwaves at eight regions at the prefrontal lobe, the frontal lobe, the temporal lobe, and the occipital lobe using brainwave measuring equipment. Brainwaves were measured for 5 minutes in a sitting position in a stable state and were also measured for 5 minutes after 15 minutes of the chudan-no-kamae movement, which is aiming at the opponent with the point of the sword while moving along eight moving lines of the opponents, and for 5 minutes after 15 minutes of three striking movements.RESULTS Alpha waves showed higher brainwave activity during the stable state than during the kendo movements (three striking movements, chudan-no-kamae) while SMR, M-beta, and H-beta showed higher brainwave activity after kendo movements than during the resting state. The asymmetry between the left and right sides increased after the movements compared to during the resting state.CONCLUSIONS These results are considered attributable to kendo training that partly increased their concentration thereby increasing brainwave activity. However, it is unclear that kendo training will be helpful for concentration through physical activities and brain activity in this study. Therefore, further study should be conducted with the measurement of factors related to emotional aspects, concentration, and brainwaves according to kendo training.